The Socio-cultural and Political Undertones in Demetillo’s Barter in Panay: An Epic - Biclar, Leo Andrew (JPAIR Multidisciplinary Research, 2014)
The Philippines, a treasury of oral folk epics, calls us for opportunities to research epics in transition, documenting and introducing them to wider audiences. Losing of the epic tradition attracts national and international attention and becomes a concern of the state and the educational system. This study is focused on the metahistorical contexts of the epic Barter in Panay by Ricaredo Demetillo (1961) who gathered his materials from Maragtas. The study is anchored to Hornedo’s (2004) theory of reality frames in teaching literature. Employing descriptive-qualitative method of research through textual analysis unfolds the value of the text as literary and fictive-historical records. The study aims to answer: How the narrative structure of the epic unveils the political and social practices of the Visayan people? How the characterization reveals the themes of the literary epic? Barter in Panay reflects the “sweetness and light” of the Filipino lifeways-its unique genetic origin and rich traditions. The voice in the epic sketches the community beyond the spatial and projects itself into the future who continues his legacy to the young listening to the tales. The epic contains historically self-aware characters providing integral engines to the Filipino identity. The study benchmarks for literary-anthropological research.